Fassi Fehri, Abdelkader. “The GENTERM Method: Automatic Generation system of Terms and Generators,” Year 3, Issue 12 (Spring 1418-1419 AH/ 1998 CE), Pp. 39-49. - الفاسي, عبد القادر الفهري (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 1998)
Abdelkader Fassi Fehri’s article is divided into five sections: a focus on terminology and its perceptions, the GENTERM (generation of terms) system, Generation of Images (GENFO), general planning for the generated term rule reinforced with a descriptive graph, and specialized languages and conceptual and epistemological components and cultural specificities. It concludes with a brief summary wherein he emphasizes that terminology should be subject to controls and systemization, that the controls stem from the general language controls, and that future terminology must be linked to automated generation given the vast number of terms needed.